Wizygoci w rejonie Bałkanów w teorii i praktyce politycznej dworów późnego cesarstwa rzymskiego - Wilczyński, Marek (Vox Patrum, 2018)
From the half of the 4-th century to the end of the 4-th century a tribe of Goths – Westgoths, played a significant role in the politics of the Eastern and Western Roman Empire courts. Activities of the emperor valens against Goths showed that regardless of military measures, an equally effective form of compulsion could also be economic actions. It was supported by an exceptional effectiveness of the trade embargo which use turned out to be much more effective measure which forced the barbarians to the obedience than acts of war. The initial politics of containment of the Goths invasion within the framework of the so called Gothic „wars” exercised by Valens was replaced by politic of opening of the borders of the Empire for Gothic immigrants in hope of strengthening of the Roman army with conscription of barbarous recruits. Lack of ability of mastering the crowds of newcomers and providing them a basis for peaceful existence ended with the tra-gedy at Adrianople in 378. A treaty of alliance of 382 seemingly met the expectations of both Parties, but for a short time only. Some attempts of the revision of the conditions of the treaty to the advantage of the Goths appeared as early as for a decade later. The key problem of the politics of the imperial courts in the Balkans at the turn of 4th and 5th century was the activity of the Visigothic king Alaricus who superbly made use of disagreements between Ravenna and Constantinople. Moreover, he made use of opportunities resulting from bestowing him a few times the rank of Roman magister militum. A controversial and still unexplained issue is, if Alaricus became the magister militum per Illyricum, already in 395 as result of negotiations with Rufin. Next disputable issue is, in which degree the ruler of the Visigoths led his own deliberate politics, and in which degree he remained a tool in hands of the politicians of the Eastern and Western Roman courts.